Evaluation of Drug Use Pattern in Emergency Department of Dilchora Referral Hospital, Dire Dawa, Ethiopia - Kirubel M. Mishore; Nigatu A. Bekele; Tsegaab Y. Yirba; Tsion F. Abone (Emergency Medicine International)
Background. Drug use evaluation is a system of continuous, systematic, criteria-based drug evaluation that ensures the appropriate use of drugs. Rationalization of drug therapy in emergency medicine would be useful in managing the broad array of conditions that present for emergency care. High-quality drug utilization is associated with the use of a relatively limited number of essential medicines. The World Health Organization developed core drug use indicators for conducting drug utilization studies in healthcare setting. WHO core drug use indicators including prescribing indicators, patient care indicators, and health facility indicators are used nowadays. Objective. The aim of this study was to evaluate the drug use pattern in the Emergency Department of Dilchora Referral Hospital, Dire Dawa, Ethiopia, 2018. Methods. A retrospective cross-sectional descriptive study was conducted in the emergency department (ED) of Dilchora Referral Hospital from July 20 to August 19, 2018, using structured data collection format. Result. Out of 344 prescriptions analyzed, a total of 753 medications were prescribed. The average number of drugs per prescription was 2.19. Of drugs prescribed, 685 (90.97%) were in their generic names. Antibiotics were prescribed in 95 (27.62%) of encounters, and injections were prescribed in 154 (44.77%) of encounters. Among 753 medications prescribed, the name and strength of drugs are indicated in 100% and 95.22%, respectively. 679 (90.17%) of drugs were prescribed from the essential drug list of Ethiopia. Conclusion. The findings of this study revealed that the drug utilization pattern was not optimal in accordance with the standard values of WHO prescribing indicators. Some of the prescribing indicators like overprescribing of antibiotics and injections were a problem. Therefore, it is very imperative for the concerned stakeholders and healthcare providers to work toward ensuring drug use according to the standard.